IncX4 Plasmid Carrying the New mcr-1.9 Gene Variant in a CTX-M-8-Producing Escherichia coli Isolate Recovered From Swine - Manageiro, Vera; Clemente, Lurdes; Romão, Raquel; Silva, Catarina; Vieira, Luís; Ferreira, Eugénia; Caniça, Manuela (Frontiers in Microbiology, 2019)
We studied a commensal colistin-resistant Escherichia coli isolated from a swine cecum sample collected at a slaughter, in Portugal. Antimicrobial susceptibility phenotype of E. coli LV23529 showed resistance to colistin at a minimum inhibitory concentration of 4 mg/L. Whole genome of E. coli LV23529 was sequenced using a MiSeq system and the assembled contigs were analyzed for the presence of antibiotic resistance and plasmid replicon types using bioinformatics tools. We report a novel mcr-1 gene variant (mcr-1.9), carried by an IncX4 plasmid, where one-point mutation at nucleotide T1238C leads to Val413Ala substitution. The mcr-1.9 genetic context was characterized by an IS26 element upstream of the mcr-pap2 element and by the absence of ISApl1. Bioinformatic analysis also revealed genes conferring resistance to β-lactams, sulphamethoxazole, trimethoprim, chloramphenicol and colistin, corresponding to the phenotype noticed. Moreover, we highlight the presence of mcr-1.9 plus blaCTX-M-8, a blaESBL gene rarely detected in Europe in isolates of animal origin; these two genes were located on different plasmids with 33,303 and 89,458 bp, respectively. MCR-1.9-harboring plasmid showed high identity to other X4-type mcr-1-harboring plasmids characterized worldwide, which strongly suggests that the presence of PMCR-encoding genes in food-producing animals, such as MCR-1.9, represent a potential threat to humans, as it is located in mobile genetic elements that have the potential to spread horizontally.